Business Model Canvas: Ceiling Fan Cleaner / Nursyafreena Rosli - Rosli, Nursyafreena (2020)
The company target employees from cleaning and services agencies. Meanwhile, the users form households. Services agencies such as cleaning agencies have many process to do. The employees must extra careful when handle this job because the blades of ceiling fan will damage or bent. This will lead to loss and Ceiling Fan Cleaner will get lowest star from the users. Furthermore, the households will get more benefit with this product which are can save their time when do a cleaning and not affected their health